Knee disorders in carpet and floor layers and painters. - Kivimaki, J.; Riihimaki, H.; Hanninen, K. (Scandinavian Journal of Work, Environment & Health, 1992)
In an evaluation of the effect of kneeling work on the knees, 168 actively working carpet and floor layers and 146 house painters were examined with the aid of a questionnaire, a clinical examination, and radiography. Reported knee pain, knee accidents, and treatment regimens for the knees were more common among the carpet and floor layers than among the painters. Radiographic changes of the tibiofemoral joint were noted equally in the two occupational groups, but osteophytes of the patella were more common among the carpet and floor layers than among the painters. In a multivariate analysis, the determinants of osteophytosis of the knee were age, occupation, knee accidents, and smoking, and osteophytosis may be due to more frequent workbreaks from kneeling postures among smoking workers. This study indicates that kneeling work increases the risk of knee disorders and such radiographic changes that might be an initial sign of knee degeneration.